1992
DOI: 10.1007/bf00686324
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of sulofenur, a novel sulfonylurea, in recurrent epithelial ovarian cancer

Abstract: A total of 16 patients with recurrent epithelial ovarian cancer were treated with sulofenur (LY 186641), a novel oral sulfonylurea. All subjects had received previous chemotherapy. Anaemia occurred in all 16 patients, 14 of whom required a blood transfusion, and 2/16 patients received methylene blue for breathlessness due to methaemaglobinaemia. Treatment was discontinued in 2/16 cases due to rising liver enzyme values, which reverted to normal on cessation of the drug. There was no nausea or alopecia. Only tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Sulofenur [( N -(5-indanesulfonyl)- N ′-(4-chlorophenyl)urea, LY18664], the prototypic member of this class ( Figure 2C ), was evaluated in clinical trials on a variety of patients with kidney (Mahjoubi et al, 1993), ovary (O’Brien et al, 1992), breast (Talbot et al, 1993), lung (Munshi et al, 1993), and stomach (Kamthan et al, 1992) cancers. It appeared that sulofenur can undergo metabolic biotransformation to yield the GSH-conjugate of p -chlorophenyl isocyanate [ S -( N - p -chlorophenylcarbamoyl) GSH, SCPG; Jochheim et al, 2002].…”
Section: Bioactivation Of Cancer Compounds By Gstmentioning
confidence: 99%
“…Sulofenur [( N -(5-indanesulfonyl)- N ′-(4-chlorophenyl)urea, LY18664], the prototypic member of this class ( Figure 2C ), was evaluated in clinical trials on a variety of patients with kidney (Mahjoubi et al, 1993), ovary (O’Brien et al, 1992), breast (Talbot et al, 1993), lung (Munshi et al, 1993), and stomach (Kamthan et al, 1992) cancers. It appeared that sulofenur can undergo metabolic biotransformation to yield the GSH-conjugate of p -chlorophenyl isocyanate [ S -( N - p -chlorophenylcarbamoyl) GSH, SCPG; Jochheim et al, 2002].…”
Section: Bioactivation Of Cancer Compounds By Gstmentioning
confidence: 99%
“…Separations were achieved with a 5 x 250-mm Synchrome Synchropak SCD-100 with 3 x 10-mm guard column (Synchropak SCD-100 packing) along with a saturation column (4 x 20 mm, Synchropak SCD-100 packing) placed between the pump and autoinjector. The LC gradient program involved initial elution with 10% acetonitrile10.025 M pH 6.5 NaP04 at 1.0 mWmin with linear change to 20% acetonitrile from 0-6 min, linear change to 35% acetonitrile from [8][9][10][11][12][13][14][15][16][17][18] min, and linear change to 50% acetonitrile from 23-29 min, where sulofenur, metabolites 2 and 3, and internal standard LY186642 had retention times of 25. 8, 15.6, 18.8, and 26.8 min, respectively. Separated plasma fractions were thawed and 25 pg of internal standard LY186642 was added to 0.3 mL of each sample.…”
Section: = '4cmentioning
confidence: 99%
“…The studies cited above used concentrations of sulofenur > 125 #M under serum-free conditions and most studies reported effects at 500 #M. Under these conditions we have shown that sulofenur causes rapid equilibration of extra cellular and intracellular pH, possibly by direct damage to the plasma membrane [21 ]. In plasma, sulofenur is highly protein-bound (> 99.9%), thereby yielding free-drug concentrations in the range of 0.5-1 /zM under therapeutic conditions [8,22]. Consequently biochemical alterations reported using concentrations of drug 1000-fold greater than those achievable in plasma probably do not relate to our proposed "site 1" target of DSU cytotoxicity that appears relevant in vivo.…”
Section: Introductionmentioning
confidence: 98%
“…In collaboration with Dr. Grindey, we demonstrated that N-(5-indanylsulfonyl)-W-(4-chlorophenyl)urea (sulofenur, ISCU) exhibited significant activity against advanced colon adenocarcinoma xenografts intrinsically resistant to virtually all standard chemotherapeutic agents [2][3][4] and also had very significant activity against several pediatric tumors grown as xenografts [5]. Clinically, sulofenur was disappointing, and although some responses were reported in phase I trials [6,7] this was not confirmed for ovarian cancer in the phase II setting [8]. Toxicity in man was due mainly to methemoglobinemia and anemia [6,9], which limited the concentrations of drug that could be achieved to levels well below those shown to elicit a therapeutic response in the xenograft models [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation